The study of the fatty acid composition of common lilac flowers of “Madame Lemoine” variety - Popyk, Аndrii; Kyslychenko, Viktoriia; Velma, Viktoriia (ScienceRise: Biological Science, 2021)
An important place in human nutrition is occupied by omega-3, omega-6 and omega-9 fatty acids (FA). They have different effects on the human body and play a significant role in the appearance and the course of some diseases (for example, cardiovascular system, gastrointestinal tract, cancer, obesity, etc.). The aim. To study the qualitative composition and the quantitative content of fatty acids in Common Lilac (Syringa vulgaris) flowers of “Madame Lemoine” variety. Materials and methods. The fatty acid composition was studied by gas chromatography based on the formation of methyl esters of fatty acids and their subsequent determination. Results and discussion. The presence and the quantitative content of 15 fatty acids have been determined. Among them, 13 FA have been identified, namely 6 saturated fatty acids and 7 unsaturated fatty acids. The total amount of saturated fatty acids (54.65 %) significantly predominates over unsaturated fatty acids (34.81 %). Palmitic acid dominates among saturated FA (39.83 %). Linoleic acid has the highest percent among unsaturated FA (13.75 %). Conclusions. For the first time the composition of fatty acids in Common Lilac flowers of “Madame Lemoine” variety has been studied. The raw material accumulates saturated fatty acids in a significant number. Palmitic acid (C 16 : 0) – 39.83 % and linoleic acid (C 18 : 2) – 13.75 % are the dominant acids